Effect Of Emotional Intelligence And Adaptation Ability On Employee Engagement Hotel Parahyangan Tasikmalaya - Rani Herlani (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This research was conducted with the aim to determine the effect of Emotional Intelligence and Adaptability on Employee Engagement Hotel Parahyangan Tasikmalaya. The method used in this study is a case study method using data obtained directly through questionnaires distributed to 32 respondents who are non-manager employees of Hotel Parahyangan Tasikmalaya. The technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that Emotional Intelligence partially has a significant effect on Employee Engagement, partially Adaptable Ability does not significantly affect Employee Engagement, simultaneously Emotional Intelligence and Adaptability have a significant effect on Employee Engagement Hotel Parahyangan Tasikmalaya.